The Influence of Work Engagement on Employee Affect and Creativity: Insights from Occupational Mental Health - Lan Ye; Yanwei Li; Na Zhang; Jian Zhang (Behavioral Sciences)
Affect plays a pivotal role in shaping employees’ work performance and mental health, with growing recognition of its capacity to drive creativity. However, the differential impacts of positive and negative affect on creative performance remain a subject of debate. This study aims to compare the relationships between high- and low-arousal affect, as well as PANA dimensions of affect, and creative performance, emphasizing the mediating role of work engagement from an occupational mental health perspective. A survey was conducted involving 278 employees and their managers across 25 companies in China. The findings reveal significant associations between high-arousal positive affect, low-arousal positive affect, high-arousal negative affect, and low-arousal negative affect with both work engagement and creative performance. Moreover, the results indicate that work engagement partially mediates the relationship between high-arousal affect and creative performance while fully mediating the relationship between low-arousal affect and creativity. These findings underscore the importance of occupational mental health—particularly work engagement—in fostering employee creativity and highlight its critical role in organizational management strategies.